Alterations in the threshold of the potassium concentration to evoke cortical spreading depression during the natural estrous cycle in mice. (November 2016) - Ebine, Taeko; Toriumi, Haruki; Shimizu, Toshihiko; Unekawa, Miyuki; Takizawa, Tsubasa; Kayama, Yohei; Shibata, Mamoru; Suzuki, Norihiro
Highlights: This study explored the inducibility of CSD in the natural estrous cycle of mice. Susceptibility to the development of CSD is elevated in the diestrus phase. Serum estrogen is significantly higher in diestrus compared to estrus. The estrogen receptor antagonist decreased the susceptibility to CSD. Neuronal excitability relevant to CSD differs among the natural estrous cycle. Abstract: Cortical spreading depression (CSD) has been implicated in a variety of neurological disorders. However, the relationship between serum sex hormones and susceptibility to the development of CSD in naturally estrous cycling female animals is largely unknown. The natural estrous cycle of mice consists of four stages, namely, proestrus, estrus, metestrus and diestrus. We measured the serum concentration of estradiol and progesterone in estrus and diestrus and compared the minimum potassium concentrations necessary to evoke CSD in each stage and in males. In diestrus, the minimum potassium concentration required to evoke CSD was significantly lower compared to the other three phases and male animals. The serum level of estradiol is significantly higher and serum level of progesterone is significantly lower in diestrus compared to estrus. Furthermore, when we administered an estrogen receptor antagonist, the susceptibility to the development of CSD was decreased. Conversely, the administration of a progesterone receptor antagonist increased the susceptibility to CSD. Our results demonstrated that neuronal excitability related to CSD induction differs among the natural estrous phases in mice.